Band Alignment Engineering by Twist Angle and Composition Modulation for Heterobilayer. Issue 29 (23rd June 2022) - Kang, Ting; Jin, Zijing; Han, Xu; Liu, Yong; You, Jiawen; Wong, Hoilun; Liu, Hongwei; Pan, Jie; Liu, Zhenjing; Tang, Tsz Wing; Zhang, Kenan; Wang, Jun; et al.
Abstract: Atomically thin monolayer semiconducting transition metal dichalcogenides (TMDs), exhibiting direct band gap and strong light‐matter interaction, are promising for optoelectronic devices. However, an efficient band alignment engineering method is required to further broaden their practical applications as versatile optoelectronics. In this work, the band alignment of two vertically stacked monolayer TMDs using the chemical vapor deposition (CVD) method is effectively tuned by two strategies: 1) formulating the compositions of MoS2(1‐x) Se2x alloys, and 2) varying the twist angles of the stacked heterobilayer structures. Photoluminescence (PL) results combined with density functional theory (DFT) calculation show that by changing the alloy composition, a continuously tunable band alignment and a transition of type II‐type I‐type II band alignment of TMD heterobilayer is achieved. Moreover, only at moderate (10°–50°) twist angles, a PL enhancement of 28%–110% caused by the type I alignment is observed, indicating that the twist angle is coupled with the global band structure of heterobilayer. A heterojunction device made with MoS0.76 Se1.24 /WS2 of 14° displays a significantly high photoresponsivity (55.9 A W −1 ), large detectivity (1.07 × 10 10 Jones), and high external quantum efficiency (135%). These findings provide engineering tools for heterostructure design for their application in optoelectronic devices. Abstract : The band alignment of transition metal dichalcogenides (TMDs) heterostructure is modulated by both twist angle and composition, realizing a transition of type II‐type I‐type II band alignment at intermediate twist angles. The discovery provides a platform for band engineering of 2D vertical TMDs heterostructures with the tunability of band alignment type, which exhibits great application potential for versatile optoelectronics.